Teachers’ Questions in EFL Classroom - Novianti Renis (PBI 15 UMY 060, 2015)
*60 Communication is an essential element of classroom life. It is needed in order to fulfill the information gap between the teachers and the students. In fact, building classroom communication is something not easy. Many classes had only one way communication where the teachers talked too much in the classroom. To solve this problem, most teachers used teachers’ questions. The researcher tried to have a research on teachers’ questions and the students’ responses to the teachers’ questions in three different classes in EFL classroom of English Education Department of Universitas Muhammadiyah Yogyakarta. A qualitative research through case studies had been chosen to answer the research. An observation was used as an instrument to collect the data. The data of the research was analyzed through the video transcripts where only whole class teacher-students interaction that was considered as questions. The result of the research indicated that knowledge questions were frequently asked by the teachers in this research. In contrast, comprehension questions, application questions, and analysis questions were rarely asked. Synthesis or creation questions and evaluation questions were hardly ever asked by the teachers. Additionally, most of all the types of teachers’ questions were responded by the students’ short responses. Keywords: Teachers’ questions, students’ responses, knowledge questions, comprehension questions, application questions, analysis questions, synthesis or creation questions, evaluation questions